Study on the Pattern of Seed Germination of Various Subspecies Cum Provenances of Acacia nilotica Willd. Ex. Del. Under Nursery Conditions - Ginwal, H. S.; Rawat, P. S.; Gera, Mohit; Gera, Neelu; Srivastava, R. L. (Indian Forester, 1995)
Seed germination pattern of 30 provenances belonging to 5 subspecies of A. nilotica namely tomentosa, indica var. jaquemontii, indica var. cuppressiformis, nilotica, and indica from 5 countries namely India, Sudan, Pakistan, Yemen and Senegal were studied in nursery conditions. Provenances of A. nilotica from Pakistan showed a very good performance and depicted a parabolic (asymptotic) type of germination curve. However subsp. indica var. cuppressiformis from Pune (Maharashtra, India) gave maximum percentage of seed germination (75%). Significantly a good correlation was evident between cumulative seed germination&number of days elapsed. Relative delay in the initiation of seed germination was found maximum in provenances of subsp. tomentosa and subsp. nilotica.